Analisis wacana : dari linguistik sampai dekonstruksi - Aminuddin; Budiman, Kris, 1964- (Yogyakarta : Diterbitkan untuk Pusat Studi Kebudayaan, Universitas Gadjah Mada, Yogyakarta oleh Kanal, 2002)
Sociolinguistics, and meaning in writing and reading process in Indonesian language.
Includes bibliographical references
Keywords: Women in literature -- Indonesia -- History and criticism; Feminism -- Indonesia -- History and criticism; Feminisim and literature -- Indonesia -- History and criticism